Synthesis and characterization of CH3NH3PbI3 and CH3NH3PbI(3-x)Clx perovskite solar cell materials - Kamonpha, Phitsamai; Padchasri, Jintara; Rujirawat, Saroj; Sukkha, Usa; Kidkhunthod, Pinit; Chanlek, Narong; Yimnirun, Rattikorn (My University, 2019)
The emerging of perovskite solar cell has attracted many interests in the synthesis and characterization of hybrid perovskite materials related to methylammonium iodide (MAI) due to various promising properties. In this work, we found a faster way to synthesize hybrid perovskite CH3NH3PbI3 and CH3NH3PbI(3-x)Clx (x = 0,1,2) powders from a different solvent in the preparation process of MAI precursor. In addition, it was found that in CH3NH3PbI(3-x)Clx powders, as characterized by XRD and XAS, with a solid-state method employed Cl atoms cannot directly substitute for I in the perovskite (ABX3) structure.
Keywords: Hybrid perovskite solar cell; MAI; XANES